Development and validation of a questionnaire to evaluate knowledge, attitude and practice (KAP) of flood disaster management (FloodDMQ-BM) among health care workers in Kelantan - Ghani, Mohd Najib Abdul (2018)
Background: Flood catastrophe has a major impact on healthcare service in Malaysia. However, there is no validated tool to measure the knowledge, attitude and practice of flood disaster management among healthcare workers involved in the response phase of a flood disaster in Malaysia.We aim to develop and validate a questionnaire in Bahasa Malaysia (FloodDMQ-BM) to measure the level of knowledge, attitude and practice of flood disaster management among healthcare workers. Materials and Methods: The questionnaire was developed based on four domains: standard operating procedure, transportation, alert system and communication. Psychometric analyses were tested on healthcare workers involved in patient management during flood disaster in Kelantan. The hypothetical concept of the items in attitude and practice sections was assessed using Exploratory Factor Analysis (EFA) and internal consistency reliability. The knowledge section was analysed using 2-parameter logistic model of Item Response Theory. Result: 36 items were generated for FloodDMQ-BM. For both the attitude and practice items, the EFA have good factor loading (>0.5) and satisfactory internal consistency of 0.925 and 0.935 respectively. The remaining items in the knowledge section have good marginal fit and adequate Root Mean Square Error of Approximation of 0.08. All the remaining items have good standardized loading (>0.3) and marginal reliability of 0.623.Conclusion: The results suggested that the FloodDMQ-BM has valid and reliable psychometric properties.